Role of Entrepreneurship Orientation And Social Media Adoption of Marketing Capability In Improving The Business Performance Of Palopo City MSMEs - Nurhidayah Nurhidayah; Rahmad Solling Hamid; I Ketut Patra (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the influence of entrepreneurial orientation and social media marketing adoption on the business performance of micro, small, and medium enterprises in Palopo City. Methodology: This study uses a quantitative approach by taking samples from business actors who are the object of the research. The data analysis techniques used include validity tests, reliability tests, classical assumption tests, and multiple linear analysis. Results: The results show that entrepreneurial orientation and social media adoption together have a significant impact on business performance. Each variable also has a positive and significant influence on improving business performance. Findings: The findings confirm that both entrepreneurial orientation and social media marketing are key drivers of MSME performance in the local context. Novelty & Originality: This study offers novelty by examining the combined effect of entrepreneurial orientation and social media adoption on MSME performance in Palopo City, a regional context rarely explored in prior research. Conclusions: The implications of this study provide an empirical basis that strengthening entrepreneurial attitudes and abilities as well as capacity building in utilizing social media strategically is an important element in increasing business competitiveness and sustainability in the digital era. Type of Paper: This paper is an empirical research paper.